2020
DOI: 10.3390/ijerph17144962
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Prevalence, and Risk Factors of Hemiplegic Shoulder Pain: A Systematic Review

Abstract: The current systematic review aimed to investigate the incidence, prevalence, and risk factors causing hemiplegic shoulder pain (HSP) after stroke. Two independent authors screened titles and abstracts for the eligibility of the included studies in the electronic databases PubMed and Web of Science. Studies which reported the incidence, prevalence, and risk factors of HSP following stroke were included. The included studies were assessed using the Newcastle–Ottawa Scale for evaluating the quality of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
3
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 52 publications
1
36
3
5
Order By: Relevance
“…In addition, based on the available evidence, we also found that the incidence and prevalence of PSSP were similar in men and women, while the incidence and prevalence of right-sided hemiplegia were higher in men. Contrary to the results reported by Anwer et al ( 49 ), some included studies ( 23 , 25 27 , 31 ) showed that patients with right-sided hemiplegia were more likely to have PSSP, possibly because of different included populations. There seemed to be three main etiological groups that may cause PSSP, namely central post-stroke pain, complex regional pain syndrome, and musculoskeletal pain (spasticity-related pain, shoulder subluxation induced pain, etc.)…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…In addition, based on the available evidence, we also found that the incidence and prevalence of PSSP were similar in men and women, while the incidence and prevalence of right-sided hemiplegia were higher in men. Contrary to the results reported by Anwer et al ( 49 ), some included studies ( 23 , 25 27 , 31 ) showed that patients with right-sided hemiplegia were more likely to have PSSP, possibly because of different included populations. There seemed to be three main etiological groups that may cause PSSP, namely central post-stroke pain, complex regional pain syndrome, and musculoskeletal pain (spasticity-related pain, shoulder subluxation induced pain, etc.)…”
Section: Discussioncontrasting
confidence: 72%
“…(50,51). Similarly, many different risk factors for PSSP have also been found (49,52). Further understanding of the etiology and risk factors of PSSP is important to minimize the risk of developing shoulder pain following a stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Shoulder pain is a common debilitating problem after stroke, with a recent metaanalysis indicating an incidence of 10%-22%. 1 There appear to be three major etiological groups that may present with hemiplegic shoulder pain (HSP), 2 namely central (central post-stroke pain, CPSP), regional (chronic regional pain syndrome, CRPS, or reflex sympathetic dystrophy, RSD), and local mechanical pain. 3 The causes of the HSP are numerous, and often overlapping.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, based on the available evidence, we also found that the incidence and prevalence of PSSP were similar in men and women, while the incidence and prevalence of rightsided hemiplegia were higher in men. Contrary to the results reported by Anwer et al (49), some included studies (23,(25)(26)(27)31) showed that patients with right-sided hemiplegia were more likely to have PSSP, possibly because of different included populations. There seemed to be three main etiological groups that may cause PSSP, namely central post-stroke pain, complex regional pain syndrome, and musculoskeletal pain (spasticityrelated pain, shoulder subluxation induced pain, etc.)…”
Section: Discussioncontrasting
confidence: 64%